2020
DOI: 10.1002/jbmr.4175
|View full text |Cite
|
Sign up to set email alerts
|

Smoking Alters Inflammation and Skeletal Stem and Progenitor Cell Activity During Fracture Healing in Different Murine Strains

Abstract: Smokers are at a higher risk of delayed union or nonunion after fracture repair. Few specific interventions are available for prevention because the molecular mechanisms that result in these negative sequelae are poorly understood. Murine models that mimic fracture healing in smokers are crucial in further understanding the local cellular and molecular alterations during fracture healing caused by smoking. We exposed three murine strains, C57BL/6J, 129X1/SvJ, and BALB/cJ, to cigarette smoke for 3 months before… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 58 publications
3
16
0
Order By: Relevance
“…Furthermore, the authors observed a significant increase in pro-inflammatory mediators and immune cell recruitment in fracture hematomas in the mice exposed to smoke. These results show the important cellular and molecular disorders that occur during fracture healing due to smoking, such as abnormal chondrogenesis, aberrant activity of skeletal stem and progenitor cells, and an intense initial inflammatory response [ 74 ]. Table 3 shows the main factors that induce and delay bone healing according to recent publications on the molecular mechanisms of bone healing.…”
Section: Factors That Delay Bone Healingmentioning
confidence: 99%
“…Furthermore, the authors observed a significant increase in pro-inflammatory mediators and immune cell recruitment in fracture hematomas in the mice exposed to smoke. These results show the important cellular and molecular disorders that occur during fracture healing due to smoking, such as abnormal chondrogenesis, aberrant activity of skeletal stem and progenitor cells, and an intense initial inflammatory response [ 74 ]. Table 3 shows the main factors that induce and delay bone healing according to recent publications on the molecular mechanisms of bone healing.…”
Section: Factors That Delay Bone Healingmentioning
confidence: 99%
“…In vivo experiment, a custom-made chamber with airflow for rats to inhale cigarette smoke continuously, was established by Chang et al, and it was found that cigarette smoke inhibited early angiogenesis using a femoral osteotomy model, analyzed by radiograph and micro-CT imaging and various biomechanical and biological tests [36]. Other experiments have also demonstrated that tobacco accelerated the pronounced initial inflammatory response [37], suppressed the immune system [38] and increased infection incidence.…”
Section: Discussionmentioning
confidence: 99%
“…26 In addition, a study conducted by Hao in 2021 in the United States showed a mean IL-1 of 100 pq/L and a median value of 80 pq/L. 27 This difference may be due to differences in the area of the wound that became the subject of each study. 25,26,27 IL-1 is known to regulate bone resorption and formation.…”
Section: Discussionmentioning
confidence: 99%
“…27 This difference may be due to differences in the area of the wound that became the subject of each study. 25,26,27 IL-1 is known to regulate bone resorption and formation. However, the results of different studies on (TNF-a), prostaglandin E2, and nitric oxide.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation